2023
DOI: 10.3390/plants12101930
|View full text |Cite
|
Sign up to set email alerts
|

A New Fluorescence Detection Method for Tryptophan- and Tyrosine-Derived Allelopathic Compounds in Barley and Lupin

Sara Leite Dias,
Adriana Garibay-Hernández,
Fabian Leon Brendel
et al.

Abstract: Barley (Hordeum vulgare) is one of the most widely cultivated crops for feedstock and beer production, whereas lupins (Lupinus spp.) are grown as fodder and their seeds are a source of protein. Both species produce the allelopathic alkaloids gramine and hordenine. These plant-specialized metabolites may be of economic interest for crop protection, depending on their tissue distribution. However, in high concentrations they pose a health risk to humans and animals that feed on them. This study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Among the 20 barley lines included in the pan-genome v1 ( 13 ), six do not contain gramine ( 1 ) or contain only traces, whereas the others produce gramine ( 1 ) in the range of 700 to 6600 pmol/mg fresh weight (FW) in the leaves ( 15 ) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 20 barley lines included in the pan-genome v1 ( 13 ), six do not contain gramine ( 1 ) or contain only traces, whereas the others produce gramine ( 1 ) in the range of 700 to 6600 pmol/mg fresh weight (FW) in the leaves ( 15 ) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…We chose the model plant A. thaliana because of the ease of the genetic transformation system that is available. After stable transformation, selected T1 plants constitutively expressing the genes AMIS , NMT , or a combination of both were tested for the presence of AMI ( 3 ) and gramine ( 1 ) by reversed-phase ultraperformance liquid chromatography fluorescence detection (RP-UPLC-FLD) ( 15 ). More than 88% ( N = 82) of the herbicide-resistant progeny of all plants transformed with the AMIS construct ( N = 92) exhibited AMI ( 3 ) concentrations above the limit of quantification.…”
Section: Resultsmentioning
confidence: 99%
“…Plant-derived allelopathic compounds have become new generation pesticides, thereby reducing the environmental stress caused by synthetic chemicals. , As a result, the secondary metabolites produced by plants are widely distributed in aquatic environments and land. , Some are toxic and have harmful effects on organisms in the environment. , GRM, a natural alkaloid obtained from Gramineae plants, has a wide application for pest control and drug development. , The alkaloid has been reported to be extensively present in agricultural land and groundwater. , Acute mortality of domestic animals has occurred through consumption of plants containing this compound. , The resistance of GRM to degradation has a negative impact on human health. Elucidation of the mechanism of hepatotoxicity caused by exposure to GRM is of great significance.…”
Section: Discussionmentioning
confidence: 99%
“…Gramine (GRM), an indole alkaloid occurring in Gramineae plants, also exhibits various pharmacological effects such as anti-inflammatory, antibacterial, antitumor, vasodilator, and bronchial smooth muscle modulator. Its derivatives have a great potential to be developed to varieties of pharmaceutical agents. In particular, GRM is a new biopesticide used to prevent brown planthoppers . Although the biopesticide has less impact on crop production than conventional pesticides, its environmental distribution has drawn public attention, due to potential environmental safety issues concerned . A survey by Swiss academics showed that GRM has been detected in the surface water around agricultural fields and grasslands, with a maximum concentration of 55 ng/mL and an average concentration of 15 ng/mL .…”
Section: Introductionmentioning
confidence: 99%